Phosphor powder, complex and light-emitting device
By introducing SCASN phosphor powder particles into the phosphor powder and controlling the carbon content, the existing red phosphor luminescence characteristics and insufficient spectral width are solved, and more efficient photoluminescence performance and better color temperature equalization are achieved.
Patent Information
- Application Number
- JP2023169436
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
In the existing white LED manufacturing, the photoluminescence characteristics and spectral width of red phosphorus are insufficient, which affects the photoluminescence efficiency and color temperature equalization.
The phosphor powder containing SCASN phosphor powder particles is used to measure its carbon content through the non-scattering infrared absorption method to ensure that the carbon content is 0.080% or below, thereby improving the photoluminescence performance of the phosphor powder.
The photoluminescence efficiency and spectral width of the phosphor powder are improved, and the optical performance and color temperature equalization of white LEDs are enhanced.
Smart Images

Figure 2025059381000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a phosphor powder, a composite, and a light-emitting device. [Background technology]
[0002] In order to manufacture white LEDs, research is being conducted on red phosphors that convert the blue light from a blue LED chip into red light. Known red phosphors include CASN phosphors and SCASN phosphors. In Patent Document 1, a nitride phosphor having a general formula M is disclosed for the purpose of providing a nitride phosphor having excellent luminescence characteristics even when excited with high-density light, particularly a narrow half-width of the emission spectrum, and a high luminescence quantum efficiency maintenance rate. a Sr b Ca c Al d S e N f It contains a crystalline phase represented by 4000 mW / mm 2 The phosphor is characterized by having a quantum efficiency maintenance rate of 85% or more when excited by light. In this general formula, M represents an activation element, and 0 <a<0.05、0.95≦b≦1、0≦c<0.1、a+b+c=1、0.7≦d≦1.3、0.7≦e≦1.3、2.5≦f≦3.5である。 [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-077800 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides a phosphor powder having improved luminescence characteristics, and a composite body and a light emitting device using the phosphor powder having improved luminescence characteristics. [Means for solving the problem]
[0005] The inventors of the present invention have intensively studied to solve the above problems. As a result, they have found that a phosphor powder containing SCASN phosphor particles, in which the carbon content in the phosphor powder measured by a carbon / sulfur simultaneous analyzer using the non-dispersive infrared absorption method is 0.080% by mass or less, can improve the light emission characteristics, and thus completed the present invention.
[0006] According to the present invention, there are provided a phosphor powder, a composite, and a light-emitting device as described below.
[0007] [1] A phosphor powder containing SCASN phosphor particles, wherein the carbon content in the phosphor powder measured by a carbon / sulfur simultaneous analyzer using the non-dispersive infrared absorption method is 0.080% by mass or less. [2] General formula, Eu a Sr b Ca c AlSi e N f O g represented by 0 < a < 1.000, 0 ≤ b < 1.000, 0 ≤ c < 1.000, 0.700 < a + b + c < 1.300, 0.700 < e < 1.300, 0 ≤ f ≤ 3.000, 0 ≤ g ≤ 3.000, 2.500 ≤ f + g ≤ 3.500, and the phosphor powder according to [1] containing the phosphor particles. [3] The phosphor powder according to [2], wherein b > 0.500. [4] The phosphor powder according to [2] or [3], wherein the molar ratio of b / (b + c) of the phosphor particles is 0.960 or more and 0.990 or less. [5] The phosphor powder according to any one of [2] to [4], wherein a < 0.300. [6] The volume-based median diameter D of the phosphor powder by the laser diffraction scattering method 50 is 1.0 μm or more and 60.0 μm or less, and the phosphor powder according to any one of [1] to [5]. [7] In the volume frequency particle size distribution of the phosphor powder by the laser diffraction scattering method, the particle diameter D at which the cumulative value becomes 10% is 10 , 90% particle diameter D 90 , median diameter D 50 Regarding (D 90 -D 10 ) / D 50 The phosphor powder according to any one of [1] to [6], wherein the value is 1.00 or more and 3.00 or less. [8] The phosphor powder according to any one of [1] to [7], which has an average diffuse reflectance of 90.0% or more at a wavelength of 700 to 800 nm measured by an ultraviolet-visible spectrophotometer. [9] The phosphor powder according to any one of [1] to [8], wherein the x value of the luminescent color in the CIE chromaticity coordinates when excited with light having a wavelength of 455 nm is 0.550 or more and 0.650 or less.
[10] The phosphor powder according to any one of [1] to [9], wherein the y value of the emitted color in the CIE chromaticity coordinates when excited with light having a wavelength of 455 nm is 0.350 or more and 0.450 or less.
[11] The phosphor powder according to any one of [1] to
[10] , which has a peak wavelength of a fluorescence spectrum measured by a spectrophotometer when irradiated with light having a wavelength of 455 nm, of 590 nm or more and 650 nm or less.
[12] The phosphor powder according to any one of [1] to
[11] , wherein the half-width of the peak of the fluorescence spectrum measured by a spectrophotometer when irradiated with light having a wavelength of 455 nm is 80.0 nm or less.
[13] A composite comprising: a phosphor powder according to any one of [1] to
[12] ; and a sealant that seals the phosphor powder.
[14] A light emitting element that emits excitation light; A complex according to
[13] , which converts the wavelength of the excitation light; A light emitting device comprising: Effect of the Invention
[0008] According to the present invention, it is possible to provide a phosphor powder having improved light-emitting properties, and a composite body and a light-emitting device using the phosphor powder having improved light-emitting properties. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view showing an example of the structure of a light emitting device according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. In the drawings, similar components are given similar symbols and descriptions thereof will be omitted as appropriate. In order to avoid complexity, when there are multiple identical components in the same drawing, only one of them may be labeled with a reference symbol, and not all of them. The drawings are for illustrative purposes only. The shapes and dimensional ratios of the components in the drawings do not necessarily correspond to the actual products.
[0011] In this embodiment, the numerical range "A to B" indicates A or more and B or less, unless otherwise specified.
[0012] <Phosphor powder> The phosphor powder of this embodiment contains SCASN phosphor particles. The SCASN phosphor particles of this embodiment are (Si,Al)-N 4 It is composed of regular tetrahedrons bonded together, and some of the Ca atoms located in the gaps of the framework are replaced by Sr atoms and form a solid solution. 2+ A part of Eu acts as a luminescence center. 2+ These are phosphor particles in which an activator element such as ZnO is substituted.
[0013] In this embodiment, whether the phosphor powder contains SCASN phosphor particles can be confirmed, for example, by the following method. First, the phosphor powder is subjected to powder X-ray diffraction using CuKα radiation using an X-ray diffractometer. Then, in the obtained X-ray diffraction pattern, the main crystal phase is CaAlSiN 3 Confirm that the diffraction pattern is the same as that of the crystal. Next, the phosphor powder is dissolved by pressurized acid decomposition to prepare a sample solution, and the obtained sample solution is subjected to quantitative analysis of Sr using an ICP optical emission spectrometer to confirm that the phosphor powder contains Sr.
[0014] The phosphor powder of this embodiment has a carbon content of 0.080 mass % or less, as measured by a non-dispersive infrared absorption method using a carbon / sulfur simultaneous analyzer.
[0015] According to the investigations of the present inventors, it has been found that in phosphor powders containing SCASN phosphor particles, there is a relationship between the carbon content of the phosphor powder and the light emitting characteristics of the phosphor powder. As a result of further investigations based on the above findings, the inventors have found that the luminescence characteristics of a phosphor powder can be improved by using the carbon content in the phosphor powder, measured by non-dispersive infrared absorption method using a simultaneous carbon / sulfur analyzer, as an indicator and setting the carbon content to 0.080 mass% or less, and have completed the present invention.
[0016] The carbon content in the phosphor powder of this embodiment, measured by a non-dispersive infrared absorption method using a carbon / sulfur simultaneous analyzer, is 0.080% by mass or less, preferably 0.070% by mass or less, more preferably 0.065% by mass or less, even more preferably 0.060% by mass or less, even more preferably 0.055% by mass or less, even more preferably 0.050% by mass or less, even more preferably 0.045% by mass or less, even more preferably 0.040% by mass or less, even more preferably 0.035% by mass or less, from the viewpoint of improving the luminescence characteristics. The lower limit of the carbon content in the phosphor powder of this embodiment is not particularly limited, but may be, for example, 0.001% by mass or more, 0.005% by mass or more, 0.010% by mass or more, 0.015% by mass or more, 0.020% by mass or more, or 0.025% by mass or more.
[0017] According to the study by the present inventors, in a phosphor powder containing SCASN phosphor particles, it is preferable that the phosphor powder has a large Sr content from the viewpoint of further improving the light emission characteristics. However, when the phosphor powder has a particularly large Sr content, the carbon content in the phosphor powder tends to increase significantly. Here, the phosphor powder having a particularly large Sr content means, for example, a phosphor powder having a general formula of Eu a Sr b Ca c Al d S e N f O g When the equation is expressed as: b>0.950. Based on the above findings, the present inventors have found that even when the phosphor powder contains a particularly large amount of Sr, the light emitting characteristics can be further improved by setting the carbon content to 0.080 mass % or less.
[0018] The phosphor powder of the present embodiment can be obtained by appropriately selecting the raw materials, the usage ratio of each raw material, the manufacturing procedure, the manufacturing conditions, and the like. Regarding the selection of the raw materials and the quantitative ratio of the raw materials, preferably, a Sr-containing raw material is used in a larger amount, a Eu-containing raw material is used in a smaller amount, and a "core" described later is added. Regarding the manufacturing procedure and the manufacturing conditions, preferably, firing is performed using a sealed container, and mixing, firing, and pulverization are performed under appropriate conditions. These details will be described later.
[0019] <Crystal structure, elemental composition, etc.> The phosphor particles of the present embodiment are composed of phosphor particles represented by the general formula Eu 3 having the same crystal phase as a Sr b Ca c AlSi e N f O g In this general formula, 0 < a < 1.000, 0 ≤ b < 1.000, 0 ≤ c < 1.000, 0.700 < a + b + c < 1.300, 0.700 < e < 1.300, 0 ≤ f ≤ 3.000, 0 ≤ g ≤ 3.000, and 2.500 ≤ f + g ≤ 3.500.
[0020] The crystal phase can be confirmed by powder X-ray diffraction. A single crystal phase of the crystal is preferable for the crystal phase, but it may contain a different phase as long as it does not significantly affect the phosphor characteristics. The presence or absence of a different phase can be determined, for example, by the presence or absence of peaks other than those due to the target crystal phase by powder X-ray diffraction.
[0021] Regarding a, from the viewpoint of further improving the light emission characteristics, preferably 0.001 < a, and preferably a < 0.300, more preferably a < 0.200, still more preferably a < 0.100, still more preferably a < 0.070, still more preferably a < 0.050, still more preferably a < 0.030, still more preferably a < 0.020, still more preferably a < 0.015, still more preferably a < 0.010, still more preferably a < 0.005, still more preferably a < 0.003.
[0022] Regarding b, from the perspective of further improving the luminescence characteristics, preferably 0 < b, more preferably 0.500 < b, still more preferably 0.700 < b, still more preferably 0.800 < b, still more preferably 0.900 < b, still more preferably 0.930 < b, still more preferably 0.940 < b, still more preferably 0.950 < b, still more preferably 0.960 < b, still more preferably 0.970 < b, and preferably b < 0.999, more preferably b < 0.995, still more preferably b < 0.990.
[0023] As another index from the perspective of "a large amount of Sr", the molar ratio of b / (b + c) is preferably 0.960 or more, more preferably 0.965 or more, still more preferably 0.970 or more, and preferably 0.990 or less, more preferably 0.985 or less, still more preferably 0.980 or less from the perspective of further improving the luminescence characteristics.
[0024] Regarding c, from the perspective of further improving the luminescence characteristics, preferably 0 < c, more preferably 0.001 < c, still more preferably 0.005 < c, still more preferably 0.010 < c, still more preferably 0.015 < c, still more preferably 0.020 < c, and preferably c < 0.200, more preferably c < 0.150, still more preferably c < 0.100, still more preferably c < 0.070, still more preferably c < 0.050, still more preferably c < 0.030.
[0025] Regarding e, from the perspective of further improving the luminescence characteristics, preferably 0.750 < e, more preferably 0.800 < e, still more preferably 0.850 < e, still more preferably 0.900 < e, and preferably e < 1.200, more preferably e < 1.100, still more preferably e < 1.000, still more preferably e < 0.970, still more preferably e < 0.950.
[0026] Regarding f, from the perspective of further improving the light-emitting characteristics, preferably 0 < f, more preferably 0.500 < f, still more preferably 1.000 < f, still more preferably 2.000 < f, still more preferably 2.500 < f, still more preferably 2.700 < f, still more preferably 2.750 < f, still more preferably 2.800 < f, and preferably f < 3.000, more preferably f < 2.980, still more preferably f < 2.960, still more preferably f < 2.950, still more preferably f < 2.930, still more preferably f < 2.900.
[0027] Regarding g, from the perspective of further improving the light-emitting characteristics, preferably 0 < g, more preferably 0.010 < g, still more preferably 0.030 < g, still more preferably 0.050 < g, still more preferably 0.060 < g, and preferably g < 3.000, more preferably g < 0.500, still more preferably g < 0.400, still more preferably g < 0.300, still more preferably g < 0.200, still more preferably g < 0.150, still more preferably g < 0.100, still more preferably g < 0.090.
[0028] Regarding a + b + c, from the perspective of further improving the light-emitting characteristics, preferably it is 0.800 or more, more preferably 0.850 or more, still more preferably 0.900 or more, still more preferably 0.950 or more, still more preferably 0.980 or more, and preferably it is 1.200 or less, more preferably 1.150 or less, still more preferably 1.100 or less, still more preferably 1.050 or less, still more preferably 1.030 or less.
[0029] With regard to f+g, from the viewpoint of further improving the light emitting characteristics, it is preferably more than 2.500, more preferably 2.600 or more, even more preferably 2.700 or more, even more preferably 2.750 or more, even more preferably 2.800 or more, even more preferably 2.850 or more, even more preferably 2.880 or more, and is preferably less than 3.500, more preferably 3.400 or less, even more preferably 3.300 or less, even more preferably 3.200 or less, even more preferably 3.100 or less, even more preferably 3.050 or less, even more preferably 3.000 or less, even more preferably 2.980 or less.
[0030] In this embodiment, the molar ratios of Eu, Sr, Ca, Al and Si among the molar ratios of each element contained in the phosphor powder can be measured, for example, by dissolving the phosphor powder by pressurized acid decomposition to prepare a sample solution, and performing quantitative analysis of the elements in the obtained sample solution using an ICP optical emission spectrometer. In this embodiment, the molar ratio of N and O among the molar ratios of each element contained in the phosphor powder can be determined, for example, by weighing out 0.03 g of the phosphor powder and measuring the oxygen and nitrogen contents using an oxygen / nitrogen analyzer.
[0031] <Particle size> The volume-based median diameter D of the phosphor powder of this embodiment measured by the laser diffraction scattering method 50 From the viewpoint of further improving the light-emitting characteristics, is preferably 1.0 μm or more, more preferably 5.0 μm or more, even more preferably 10.0 μm or more, even more preferably 15.0 μm or more, even more preferably 20.0 μm or more, even more preferably 23.0 μm or more, and is preferably 60.0 μm or less, more preferably 50.0 μm or less, even more preferably 45.0 μm or less, even more preferably 40.0 μm or less, even more preferably 35.0 μm or less, even more preferably 33.0 μm or less.
[0032] In the volume frequency particle size distribution of the phosphor powder of this embodiment by the laser diffraction scattering method, the particle diameter D at which the cumulative value becomes 10% 10From the viewpoint of further improving the light-emitting characteristics, is preferably 0.1 μm or more, more preferably 1.0 μm or more, even more preferably 3.0 μm or more, even more preferably 5.0 μm or more, even more preferably 7.0 μm or more, even more preferably 9.0 μm or more, even more preferably 10.0 μm or more, and is preferably 30.0 μm or less, more preferably 25.0 μm or less, even more preferably 20.0 μm or less, even more preferably 17.0 μm or less, even more preferably 15.0 μm or less.
[0033] In the volume frequency particle size distribution of the phosphor powder of this embodiment by the laser diffraction scattering method, the particle diameter D at which the cumulative value is 90% 90 From the viewpoint of further improving the light-emitting characteristics, is preferably 10.0 μm or more, more preferably 20.0 μm or more, even more preferably 30.0 μm or more, even more preferably 40.0 μm or more, even more preferably 45.0 μm or more, even more preferably 50.0 μm or more, even more preferably 53.0 μm or more, and is preferably 100.0 μm or less, more preferably 90.0 μm or less, even more preferably 80.0 μm or less, even more preferably 75.0 μm or less, even more preferably 70.0 μm or less, even more preferably 67.0 μm or less.
[0034] In the volume frequency particle size distribution of the phosphor powder of this embodiment, measured by a laser diffraction scattering method, (D 90 -D 10 ) / D 50 From the viewpoint of further improving the light-emitting characteristics, the value of is preferably 1.00 or more, more preferably 1.10 or more, even more preferably 1.20 or more, even more preferably 1.25 or more, even more preferably 1.30 or more, even more preferably 1.35 or more, even more preferably 1.38 or more, and is preferably 3.00 or less, more preferably 2.70 or less, even more preferably 2.50 or less, even more preferably 2.30 or less, even more preferably 2.20 or less, and even more preferably 2.10 or less.
[0035] In this embodiment, D 50 , D 10 and D. 90The particle size distribution of the above can be adjusted by appropriately applying known means such as pulverization, sieving, etc. Details will be described later.
[0036] <Diffuse reflectance> The average diffuse reflectance of the phosphor powder of this embodiment at a wavelength of 700 to 800 nm measured by an ultraviolet-visible spectrophotometer is preferably 90.0% or more, more preferably 91.0% or more, even more preferably 92.0% or more, even more preferably 93.0% or more, even more preferably 94.0% or more, even more preferably 95.0% or more, and even more preferably 95.5% or more, from the viewpoint of further improving the light-emitting characteristics. The upper limit of the average diffuse reflectance of the phosphor powder of this embodiment at a wavelength of 700 to 800 nm is not particularly limited, but may be, for example, 99.0% or less, 98.0% or less, or 97.0% or less.
[0037] In this embodiment, the average diffuse reflectance of the phosphor powder at a wavelength of 700 to 800 nm can be determined, for example, by the following method. First, a UV-Vis spectrophotometer equipped with an integrating sphere is used to perform baseline correction with a standard reflector (Spectralon), a solid sample holder filled with phosphor powder is set, and diffuse reflectance is measured in the wavelength range of 450 to 800 nm. Next, the average value of the measurement results in the range of 700 to 800 nm is calculated, and this is taken as the average diffuse reflectance in the wavelength range of 700 to 800 nm.
[0038] <Chromaticity> The x value in the CIE chromaticity coordinates of the emitted color of the phosphor powder of this embodiment when excited with light having a wavelength of 455 nm is, from the viewpoint of further improving the luminous characteristics, preferably 0.550 or more, more preferably 0.560 or more, even more preferably 0.570 or more, even more preferably 0.580 or more, even more preferably 0.590 or more, and is preferably 0.650 or less, more preferably 0.640 or less, even more preferably 0.630 or less, even more preferably 0.620 or less, even more preferably 0.610 or less.
[0039] The y value in the CIE chromaticity coordinates of the emitted color of the phosphor powder of this embodiment when excited with light having a wavelength of 455 nm is, from the viewpoint of further improving the luminous characteristics, preferably 0.350 or more, more preferably 0.360 or more, even more preferably 0.370 or more, even more preferably 0.380 or more, even more preferably 0.390 or more, and is preferably 0.450 or less, more preferably 0.440 or less, even more preferably 0.430 or less, even more preferably 0.420 or less, and even more preferably 0.410 or less.
[0040] In this embodiment, the x and y values in the CIE chromaticity coordinates of the luminescent color when excited with light having a wavelength of 455 nm can be determined, for example, by the following method. First, the emission spectrum of the phosphor powder at an excitation wavelength of 455 nm is measured using a solid sample holder attached to a spectrofluorophotometer corrected with Rhodamine B and a secondary standard light source. Next, the x and y values of the CIE chromaticity coordinates in the XYZ color system specified in JIS Z8701:1999 are calculated from the range of 465 nm to 780 nm of the obtained emission spectrum in accordance with JIS Z8724:1997.
[0041] <Absorption rate> From the viewpoint of further improving the light emission characteristics, the absorptance of the phosphor powder of this embodiment for light having a wavelength of 455 nm is preferably 70.0% or more, more preferably 75.0% or more, even more preferably 78.0% or more, even more preferably 80.0% or more, and even more preferably 84.0% or more. The upper limit of the absorptance of the phosphor powder of this embodiment for light having a wavelength of 455 nm is not particularly limited, and may be, for example, 99.9% or less, 99.0% or less, 95.0% or less, or 90.0% or less.
[0042] In this embodiment, the absorptance of the phosphor powder with respect to light having a wavelength of 455 nm can be determined, for example, by the following method. First, the phosphor powder is filled into a concave cell so that the surface is smooth, and then the cell is attached to the opening of the integrating sphere. Next, monochromatic light with a wavelength of 455 nm is split from a Xe lamp, which is the light source, and introduced into the integrating sphere using an optical fiber as excitation light for the phosphor. The phosphor powder is irradiated with this monochromatic excitation light, and the fluorescence spectrum is measured using a spectrophotometer. From the obtained fluorescence spectrum data, the emission intensity of the phosphor powder is determined, and the number of reflected excitation light photons (Qref) and the number of fluorescence photons (Qem) are calculated. The number of reflected excitation light photons is calculated in the wavelength range of 450 to 465 nm, and the number of fluorescence photons is calculated in the range of 465 to 800 nm. In addition, using the same device, a standard reflector with a reflectance of 99% is attached to the opening of the integrating sphere to measure the spectrum of excitation light with a wavelength of 455 nm. At that time, the number of excitation light photons (Qex) is calculated from the spectrum in the wavelength range of 450 to 465 nm. From the above calculation results, the absorptance of the phosphor for 455 nm light is calculated based on the following formula. Absorption rate for 455 nm light = ((Qex-Qref) / Qex) x 100
[0043] <Internal quantum efficiency> From the viewpoint of further improving the light emission characteristics, the internal quantum efficiency of the phosphor powder of this embodiment when excited by light having a wavelength of 455 nm is preferably 78.0% or more, more preferably 80.0% or more, even more preferably 82.0% or more, even more preferably 83.0% or more, even more preferably 84.0% or more, and even more preferably 85.0% or more. The upper limit of the internal quantum efficiency of the phosphor powder of this embodiment when excited by light having a wavelength of 455 nm is not particularly limited, but may be, for example, 99.9% or less, 99.0% or less, 95.0% or less, or 90.0% or less.
[0044] In this embodiment, the internal quantum efficiency of the phosphor powder when excited by light with a wavelength of 455 nm can be calculated, for example, based on the calculation results of the number of reflected excited light photons (Qref), the number of fluorescent photons (Qem), and the number of excited light photons (Qex) described above, based on the calculation formula shown below. Internal quantum efficiency = (Qem / (Qex-Qref)) x 100
[0045] <External quantum efficiency> From the viewpoint of further improving the light emission characteristics, the external quantum efficiency of the phosphor powder of this embodiment when excited by light having a wavelength of 455 nm is preferably 65.0% or more, more preferably 67.0% or more, even more preferably 69.0% or more, even more preferably 70.5% or more, and even more preferably 71.5% or more. The upper limit of the external quantum efficiency of the phosphor powder of this embodiment when excited by light having a wavelength of 455 nm is not particularly limited, but may be, for example, 99.9% or less, 99.0% or less, 95.0% or less, 90.0% or less, 85.0% or less, or 80.0% or less.
[0046] In this embodiment, the external quantum efficiency of the phosphor powder when excited by light with a wavelength of 455 nm can be calculated, for example, based on the calculation results of the number of reflected excited light photons (Qref), the number of fluorescent photons (Qem), and the number of excited light photons (Qex) described above, based on the calculation formula shown below. External quantum efficiency = (Qem / Qex) x 100 From the above formula, the relationship between the external quantum efficiency, the absorptance for 455 nm light, and the internal quantum efficiency can be expressed as follows: External quantum efficiency = absorptivity for 455 nm light × internal quantum efficiency
[0047] <Peak wavelength, half-width> From the viewpoint of further improving the light-emitting characteristics, the peak wavelength of the fluorescence spectrum when the phosphor powder of this embodiment is irradiated with light having a wavelength of 455 nm is preferably 590 nm or more, more preferably 595 nm or more, even more preferably 600 nm or more, even more preferably 605 nm or more, and preferably 650 nm or less, more preferably 640 nm or less, even more preferably 630 nm or less, even more preferably 625 nm or less, even more preferably 620 nm or less, and even more preferably 615 nm or less.
[0048] The half-width of the peak of the fluorescence spectrum when the phosphor powder of this embodiment is irradiated with light having a wavelength of 455 nm is preferably 80.0 nm or less, more preferably 78.0 nm or less, even more preferably 77.0 nm or less, even more preferably 76.0 nm or less, even more preferably 75.0 nm or less, even more preferably 74.5 nm or less, and even more preferably 74.0 nm or less, from the viewpoint of further improving the light-emitting characteristics. The lower limit of the half-width of the peak of the fluorescence spectrum when the phosphor powder of this embodiment is irradiated with light having a wavelength of 455 nm is not particularly limited, but may be, for example, 30.0 nm or more, 50.0 nm or more, 60.0 nm or more, or 65.0 nm or more.
[0049] In this embodiment, the fluorescence spectrum when the phosphor powder is irradiated with light having a wavelength of 455 nm can be measured, for example, by a method similar to the above-mentioned method for measuring the absorptance.
[0050] <Relative fluorescence intensity> From the viewpoint of further improving the light emitting characteristics, the relative fluorescence intensity of the phosphor powder of this embodiment is preferably 200% or more, more preferably 205% or more, even more preferably 208% or more, even more preferably 210% or more, even more preferably 215% or more, and even more preferably 220% or more. The upper limit of the relative fluorescence intensity of the phosphor powder of this embodiment is not particularly limited, and may be, for example, 400% or less, 350% or less, 300% or less, 270% or less, or 250% or less.
[0051] In this embodiment, the relative fluorescence intensity of the phosphor powder can be calculated by taking the peak intensity of the emission spectrum obtained by irradiating YAG:Ce with monochromatic light of 455 nm as 100%, and expressing the peak intensity in the fluorescence spectrum measured by the same method as the above-mentioned method for measuring the absorptance as a relative peak intensity (%). In other words, the relative fluorescence intensity Y 1 is a relative value to a standard sample.
[0052] <Method of manufacturing phosphor powder> The phosphor powder of this embodiment can be obtained by appropriately selecting raw materials, the ratio of each raw material, the manufacturing procedure, the manufacturing conditions, etc. Specifically, the phosphor powder of this embodiment is preferably A mixing step of mixing the starting materials to obtain a raw material mixture powder; A sintering process for sintering the raw material powder mixture to obtain a lump of sintered powder; A powdering process for powdering the lump-shaped fired powder; The phosphor powder can be produced through the steps. In addition, the phosphor powder may be produced through additional steps other than those described above.
[0053] According to the study by the present inventors, it has been found that when the phosphor powder contains a particularly large amount of Sr, the carbon content in the phosphor powder tends to increase significantly. a Sr b Ca c Al d S e N f O g When the equation is expressed as: b>0.950. Even when the phosphor powder of this embodiment has a particularly large Sr content, the carbon content can be controlled to 0.080 mass% or less by appropriately selecting the raw materials described below, the usage ratio of each raw material, the manufacturing procedure, and the manufacturing conditions.
[0054] <Mixing process> In the mixing step of this embodiment, the starting materials are mixed to form a raw material mixed powder. From the viewpoint of further improving the luminescence characteristics of the phosphor powder, the starting material of this embodiment preferably contains all of a europium compound, a strontium compound, a calcium compound, silicon nitride and aluminum nitride, and more preferably contains all of europium oxide, strontium nitride, calcium nitride, silicon nitride and aluminum nitride. Each starting material in this embodiment is preferably in powder form.
[0055] From the perspective of further improving the luminescence properties, the europium compound of this embodiment preferably contains, alone, one selected from the group consisting of europium oxide, europium nitride, and europium fluoride, and more preferably contains europium oxide alone.
[0056] In the firing process of this embodiment, europium can be divided into those that dissolve, those that volatilize, and those that remain as heterogeneous components. The heterogeneous components containing europium can be removed by acid treatment or the like. However, if too much heterogeneous components containing europium are generated, components insoluble in acid treatment are generated, resulting in a decrease in luminance. Also, if it is a heterogeneous phase that does not absorb excess light, it may remain as it is, and europium may be contained in this heterogeneous phase.
[0057] From the perspective of further improving the luminescence properties, the amount of the europium compound of this embodiment is preferably used in an amount such that 0.001 < a < 0.010, more preferably 0.001 < a < 0.005, for a in the aforementioned general formula in the charging ratio. Incidentally, when using the core particles described later, the amount of europium in the core particles is not included in a in the above inequality.
[0058] On the other hand, from the perspective of further improving the luminescence properties, the amount of the strontium compound of this embodiment is preferably used in an amount such that 0.900 < b < 1.000, more preferably 0.950 < b < 0.990, for b in the aforementioned general formula in the charging ratio. Incidentally, when using the core particles described later, the amount of strontium in the core particles is not included in b in the above inequality.
[0059] On the other hand, from the perspective of further improving the luminescence properties, the amount of the calcium compound of this embodiment is preferably used in an amount such that 0.010 < c < 0.040, more preferably 0.020 < c < 0.030, for c in the aforementioned general formula in the charging ratio. Incidentally, when using the core particles described later, the amount of strontium in the core particles is not included in c in the above inequality.
[0060] The starting material (mixed raw material powder) of this embodiment preferably contains SCASN phosphor core particles having a median diameter of 10 μm or more and 20 μm or less. In other words, a part of the starting material is preferably SCASN phosphor core particles having a median diameter of 10 μm or more and 20 μm or less. From the viewpoint of further improving the light emitting characteristics, the median diameter of the SCASN phosphor core particles of this embodiment is preferably 10 μm or more, more preferably 14 μm or more, and is preferably 20 μm or less, more preferably 18 μm or less. In this specification, the SCASN phosphor core particle is also referred to simply as a "core particle" or "core".
[0061] Although the details are unclear, it is believed that by using core particles, crystallization will proceed from the core particles in the subsequent firing process. For this reason, it is believed that the way crystals grow will be different from when the firing process is carried out without using core particles (for example, it is believed that by using cores, the composition of each particle will be more uniform than when no cores are used). And, perhaps as a result, it is believed that it will be easier to obtain phosphor powder with improved luminescence properties.
[0062] The core particles of this embodiment can be, for example, a phosphor powder represented by the same general formula as the phosphor powder of this embodiment described above. In other words, the core particles have the same or similar composition as the phosphor powder of this embodiment, although the carbon content in the phosphor powder is not necessarily 0.080 mass% or less, as measured by a non-dispersive infrared absorption method using a carbon / sulfur simultaneous analyzer.
[0063] When core particles are used, the amount thereof is, from the viewpoint of further improving the luminescence characteristics, preferably 3 mass % or more, more preferably 5 mass % or more, even more preferably 8 mass % or more, and preferably 30 mass % or less, more preferably 20 mass % or less, even more preferably 15 mass % or less, even more preferably 12 mass % or less, based on the total amount of the raw material mixed powder.
[0064] The core particles can be obtained, for example, through a process almost similar to that of the phosphor powder of this embodiment. That is, in the manufacturing process of the phosphor powder of this embodiment, the core particles can be obtained in the same manner except that the core particles are not added in the mixing process. The composition (general formula) of the core particles is also preferably the same as that of the phosphor powder of this embodiment.
[0065] In the mixing step of this embodiment, the raw material mixed powder can be obtained, for example, by a method of dry mixing the starting materials, or a method of wet mixing in an inert solvent that does not substantially react with each starting material and then removing the solvent. As a mixing device, for example, a small mill mixer, a V-type mixer, a rocking mixer, a ball mill, a vibration mill, etc. can be used. After mixing using the device, the raw material mixed powder can be obtained by removing aggregates using a sieve as necessary. In order to prevent deterioration of the starting materials and unintended inclusion of oxygen, the mixing step of this embodiment is preferably carried out in a nitrogen atmosphere or in an environment with as little moisture (humidity) as possible.
[0066] <Firing process> In the firing step of this embodiment, the raw material mixed powder obtained in the mixing step is fired to obtain a fired powder. In order to further improve the luminescence characteristics, the sintering temperature in the sintering step of this embodiment is preferably 1850°C or higher, more preferably 1900°C or higher, and preferably 2050°C or lower, more preferably 2000°C or lower. When the sintering temperature is equal to or higher than the lower limit, the grain growth of the phosphor particles proceeds more effectively. Therefore, the luminescence characteristics of the phosphor powder can be further improved. When the sintering temperature is equal to or lower than the upper limit, the decomposition of the phosphor particles can be further suppressed. Therefore, the luminescence characteristics of the phosphor powder can be further improved.
[0067] The heating and holding time in the firing step of this embodiment is preferably 5 hours or more, more preferably 7 hours or more, and preferably 15 hours or less, and further preferably 10 hours or less, from the viewpoint of further improving the luminescence characteristics. From the viewpoint of further improving the luminescence characteristics, the pressure in the firing step of this embodiment is preferably 0.7 MPaG or more, more preferably 0.8 MPaG or more, and is preferably 1 MPaG or less, more preferably 0.9 MPaG or less. From the viewpoint of controlling the oxygen concentration, the firing step of this embodiment is preferably performed in a nitrogen gas atmosphere, that is, in a nitrogen gas atmosphere with a pressure of 0.7 MPaG or more and 1 MPaG or less.
[0068] In the firing step of this embodiment, in order to further improve the luminescence characteristics, it is preferable to fill the mixture in a container that is unlikely to react with the raw material mixed powder during firing and heat it. Specifically, it is preferable to use a high melting point container, and more preferably a tungsten container. This can suppress the generation of heterogeneous phases.
[0069] In addition, in the firing step of this embodiment, from the viewpoint of further improving the luminescence characteristics, the above-mentioned container is preferably a sealed container with high airtightness. By firing the raw material mixed powder under sealed conditions, it is possible to prevent the intrusion of carbon, oxygen, moisture (humidity), etc. into the container and suppress the deterioration of the raw material mixed powder, thereby further improving the luminescence characteristics of the phosphor powder. Even when the phosphor powder contains a particularly large amount of Sr and the carbon content in the phosphor powder is likely to increase significantly, the increase in the carbon content in the phosphor powder can be suppressed by firing the raw material powder mixture under sealed conditions.
[0070] The structure of the sealed container is preferably such that the inside of the container is sealed by narrowing the gap between the lid and the body of the container. As a method for narrowing the gap between the lid and the body of the sealed container, for example, a method of making the body and the lid of the container fit together, whereas a conventional container has a structure in which the lid is simply placed on the body, can be mentioned.
[0071] <Powderization process> In the pulverization step of this embodiment, the sintered powder is once pulverized by using a single or a combination of processes such as crushing, grinding, and classification. Since the sintered powder obtained through the sintering step is usually a sintered mass, the sintered powder is pulverized to make it easier to handle.
[0072] A specific processing method for the powdering step of this embodiment is, for example, a method of pulverizing the sintered body to a predetermined particle size using a general pulverizer such as a ball mill, a vibration mill, a jet mill, etc. However, care should be taken because excessive pulverization may generate fine particles that easily scatter light or may cause crystal defects on the particle surface, resulting in a decrease in luminous efficiency.
[0073] <Annealing process> In the method for producing phosphor powder of this embodiment, after the powdering step, an annealing step may be performed in which the fired powder is annealed at a temperature lower than the firing temperature in the firing step. This can sufficiently improve the luminous efficiency of the phosphor powder, and also can improve the luminous properties of the phosphor powder by removing distortions and defects caused by the rearrangement of the elements. On the other hand, the annealing step may result in the generation of heterogeneous phases, but these can be sufficiently removed by the acid treatment step described below.
[0074] The annealing step of the present embodiment is more preferably performed in the air under atmospheric pressure in order to further improve the light emitting characteristics.
[0075] From the viewpoint of further improving the light emitting characteristics, the heat treatment temperature in the annealing step of this embodiment is preferably 1250° C. or higher, more preferably 1300° C. or higher, and preferably 1450° C. or lower, more preferably 1400° C. or lower. From the viewpoint of further improving the light emitting properties, the heat treatment time in the annealing step of this embodiment is preferably 5 hours or more, more preferably 7 hours or more, and preferably 10 hours or less, and further preferably 9 hours or less.
[0076] In the annealing step of this embodiment, similarly to the sintering step, it is preferable to fill the mixture in a container that is unlikely to react with the sintered powder during heat treatment, for example, a high-melting-point container, specifically a container whose inner wall is made of tungsten, and heat it. In order to further improve the light-emitting properties, it is preferable that the container used in the annealing step is a sealed container as described above, and it is more preferable that both the containers used in the firing step and the annealing step are sealed containers.
[0077] <Acid treatment process> In the method for producing phosphor powder of this embodiment, an acid treatment step of treating the phosphor powder with acid may be performed. This makes it possible to remove at least a portion of the impurities that do not contribute to light emission. Incidentally, it is presumed that the impurities that do not contribute to light emission are generated during the firing and annealing steps.
[0078] In the acid treatment step of the present embodiment, an aqueous solution containing one or more acids selected from the group consisting of hydrofluoric acid, sulfuric acid, phosphoric acid, hydrochloric acid, and nitric acid can be used as the acid. In particular, from the viewpoint of further improving the luminescence characteristics, the aqueous solution preferably contains hydrochloric acid, hydrofluoric acid, nitric acid, or a mixed acid of hydrofluoric acid and nitric acid, and more preferably contains hydrochloric acid.
[0079] The acid treatment step of this embodiment can be carried out by dispersing the annealed powder in an aqueous solution containing the above-mentioned acid. From the viewpoint of further improving the luminescence characteristics, the stirring time is preferably 30 minutes or more, more preferably 45 minutes or more, and preferably 3 hours or less, more preferably 2 hours or less. From the viewpoint of further improving the luminescence characteristics, the stirring temperature is preferably 50°C or more, more preferably 60°C or more, and preferably 100°C or less, more preferably 90°C or less.
[0080] After the acid treatment step of this embodiment, the liquid in which the annealed powder is dispersed may be boiled, and substances other than the phosphor powder may be separated by filtration, and substances attached to the phosphor particles may be washed with water as necessary. After washing with water, the phosphor powder is usually dried by natural drying or drying in a dryer. The dried phosphor powder may be placed in a crucible and heated to modify the surface.
[0081] (Elutriation process) In the method for producing phosphor powder of the present embodiment, after the acid treatment step, an elutriation step may be performed to remove fine particles from the acid-treated powder by elutriation. This makes it possible to remove fine particles that may deteriorate the luminescence characteristics of the phosphor powder, thereby further improving the luminescence characteristics.
[0082] The elutriation step of this embodiment is carried out by putting the acid-treated powder into a dispersion medium, preparing a dispersion liquid, stirring the mixture, precipitating the acid-treated powder in the dispersion liquid, and removing the supernatant. After removing the supernatant, the precipitate is collected by filtration and dried to obtain an acid-treated powder from which the fine particle powder has been removed. In the elutriation step, the above-mentioned preparation of the dispersion liquid and removal of the supernatant may be repeated. As the dispersion medium, it is preferable to use water or an aqueous solution of sodium hexametaphosphate from the viewpoint of further improving the luminescence characteristics.
[0083] <Complex> The composite of the present embodiment includes, for example, the above-described phosphor powder and a sealant that seals the phosphor powder. In the composite of the present embodiment, the above-described phosphor powder is dispersed in the sealant. From the viewpoint of further improving the light emitting properties of the composite, the sealing material of the present embodiment preferably contains one or more materials selected from the group consisting of silicone resin, epoxy resin, urethane resin, glass and ceramics.
[0084] The content of the phosphor powder in the composite of this embodiment, when the total amount of the composite is taken as 100 mass%, is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 1 mass% or more, from the viewpoint of further improving the luminescence characteristics of the composite, and is preferably 20 mass% or less, more preferably 15 mass% or less, even more preferably 10 mass% or less, even more preferably 5 mass% or less.
[0085] The composite of this embodiment can be produced by adding the phosphor powder of this embodiment to liquid resin, glass, ceramics, etc., mixing them uniformly, and then curing or sintering them by heat treatment.
[0086] <Light emitting device> The light emitting device of the present embodiment includes a light emitting element that emits excitation light, and the composite of the present embodiment that converts the wavelength of the excitation light. The light emitting device of this embodiment will be described below with reference to Fig. 1, which is a schematic cross-sectional view showing an example of the structure of the light emitting device of this embodiment. As shown in Fig. 1, the light emitting device 100 includes a light emitting element 120, a heat sink 130, a case 140, a first lead frame 150, a second lead frame 160, a bonding wire 170, a bonding wire 172, and a composite body 40.
[0087] The light emitting element 120 is mounted in a predetermined region on the upper surface of the heat sink 130. By mounting the light emitting element 120 on the heat sink 130, it is possible to improve the heat dissipation properties of the light emitting element 120. Note that a packaging substrate may be used instead of the heat sink 130.
[0088] The light emitting element 120 is a semiconductor element that emits excitation light. For example, an LED chip that emits light with a wavelength of 300 nm to 500 nm, which corresponds to near ultraviolet to blue light, can be used as the light emitting element 120. One electrode (not shown) disposed on the upper surface side of the light emitting element 120 is connected to the surface of the first lead frame 150 via a bonding wire 170 such as a gold wire. The other electrode (not shown) formed on the upper surface of the light emitting element 120 is connected to the surface of the second lead frame 160 via a bonding wire 172 such as a gold wire.
[0089] A generally funnel-shaped recess whose hole diameter gradually increases from the bottom surface toward the top is formed in the case 140. The light emitting element 120 is provided on the bottom surface of the recess. The wall surface of the recess surrounding the light emitting element 120 serves as a reflector.
[0090] The composite 40 is filled in the recess whose wall is formed by the case 140. The composite 40 is a wavelength conversion member that converts the excitation light emitted from the light emitting element 120 into light with a longer wavelength. The composite of this embodiment is used as the composite 40, and the above-mentioned phosphor powder 1 is dispersed in the sealing material 30 such as a resin. The light emitting device 100 emits a mixed color of the light of the light emitting element 120 and the light generated from the phosphor powder 1 that is excited by absorbing the light of the light emitting element 120. In order to obtain white as the mixed color (to make the light emitting device 100 a white LED), it is preferable that the composite 40 contains, for example, LuAG phosphor powder in addition to the phosphor powder 1 (it is preferable that LuAG phosphor powder is dispersed in the sealing material 30 in addition to the phosphor powder 1). In this embodiment, since the peak wavelength and the half width of the fluorescence spectrum of the phosphor powder 1 are within certain numerical ranges, good white light can be easily obtained.
[0091] 1 shows a surface-mounted light-emitting device, but the light-emitting device is not limited to the surface-mounted type. The light-emitting device may be a bullet type, a COB (chip-on-board) type, a CSP (chip-scale package) type, or the like.
[0092] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0093] The embodiments of the present invention will be described in detail based on examples and comparative examples. However, the present invention is not limited to the examples.
[0094] Example 1 <Preparation of nucleating agent> First, put 61.38 g of α-type silicon nitride (Si 3 N 4 , Ube Industries, Ltd., SN-E10 grade), 53.80 g of aluminum nitride (AlN, Tokuyama Corporation, E grade) and 0.92 g of europium oxide (Eu 2 O 3 (manufactured by Shin-Etsu Chemical Co., Ltd.) was added and premixed.
[0095] Next, in a glove box maintained in a nitrogen atmosphere in which the moisture content was adjusted to 1 mass ppm or less and the oxygen concentration was adjusted to 50 mass ppm or less, 2.98 g of calcium nitride (Ca 3 N 2 , Materion) and 120.91 g of strontium nitride (Sr 3 N 2 (manufactured by Kojundo Chemical Laboratory, purity 2N) was further added and dry mixed to obtain a mixture.
[0096] In a glove box, 240 g of the mixture was filled into a sealed container made of tungsten. After closing the lid of the sealed container, it was removed from the glove box and placed in an electric furnace equipped with a carbon heater. Then, the electric furnace was fully evacuated until the pressure inside the furnace was 0.1 PaG or less. Here, the sealed container has a structure in which the main body and the lid are fitted together, so that the gap between the lid and the main body is narrower than that of conventional containers, and the sealing performance is improved.
[0097] While continuing the vacuum evacuation, the temperature in the electric furnace was raised to 600°C. After reaching 600°C, nitrogen gas was introduced into the electric furnace, and the pressure in the electric furnace was adjusted to 0.85MPaG. Then, under a nitrogen gas atmosphere, the temperature in the electric furnace was raised to 1950°C, and after reaching 1950°C, heat treatment was carried out for 8 hours. Then, heating was terminated and the material was cooled to room temperature. After cooling to room temperature, red lumps were collected from the container. The collected lumps were crushed and sieved in a mortar to prepare core particles (nucleating agent) with a median diameter of 17μm.
[0098] <Production of phosphor powder> In a container, 54.96 g of α-type silicon nitride (Si 3 N 4 , Ube Industries, Ltd., SN-E10 grade), 48.18 g of aluminum nitride (AlN, Tokuyama Corporation, E grade), 0.41 g of europium oxide (Eu 2 O 3 , manufactured by Shin-Etsu Chemical Co., Ltd.) and 24.00 g of the nucleating agent prepared as described above were each weighed out and premixed.
[0099] Next, in a glove box maintained in a nitrogen atmosphere in which the moisture content was adjusted to 1 mass ppm or less and the oxygen concentration was adjusted to 50 mass ppm or less, 1.34 g of calcium nitride (Ca 3 N 2 , Materion) and 111.11 g of strontium nitride (Sr 3 N 2 (Koujundo Chemical Laboratory Co., Ltd., purity 2N) was further weighed out and dry mixed. A mixed powder was obtained. Table 1 shows the relationship between the amount of nucleating agent and raw material powder (mass%) and the breakdown of the amount of each element in the raw material powder (molar ratio).
[0100] In a glove box, 240 g of the mixed powder was filled into a sealed container made of tungsten. After closing the lid of the sealed container, it was removed from the glove box and placed in an electric furnace equipped with a carbon heater. Then, the electric furnace was evacuated sufficiently until the pressure inside the electric furnace became 0.1 PaG or less.
[0101] While continuing the vacuum evacuation, the temperature in the electric furnace was raised to 600°C. After reaching 600°C, nitrogen gas was introduced into the electric furnace, and the pressure in the electric furnace was adjusted to 0.85MPaG. Then, in a nitrogen gas atmosphere, the temperature in the electric furnace was raised to 1950°C, and after reaching 1950°C, heat treatment was performed for 8 hours. Then, heating was stopped and the material was cooled to room temperature. After cooling to room temperature, red lumps were collected from the container. The collected lumps were crushed, sieved, and the particle size was adjusted to obtain the phosphor powder of Example 1.
[0102] The obtained phosphor sample was subjected to powder X-ray diffraction using CuKα radiation using an X-ray diffractometer (Ultima IV manufactured by Rigaku Corporation). The obtained X-ray diffraction pattern was 3 The diffraction pattern is identical to that of the crystal, and the main crystalline phase is CaAlSiN 3 It was confirmed that the crystal structure was the same as that of the crystal.
[0103] Example 2 A phosphor powder of Example 2 was obtained in the same manner as in Example 1, except that in the mixing step, core particles having a particle size of 15 μm were added instead of core particles having a particle size of 17 μm.
[0104] Example 3 A phosphor powder of Example 3 was obtained in the same manner as in Example 1, except that no core particles were added in the mixing step.
[0105] Comparative Example 1 The phosphor powder of Comparative Example 1 was obtained in the same manner as in Example 1, except that in the mixing step, 54.64 g of α-type silicon nitride, 47.89 g of aluminum nitride, 0.41 g of europium oxide, 24.00 g of nucleating agent, and 113.06 g of strontium nitride were mixed, and calcium nitride was not mixed, and in the firing step, a non-sealed tungsten container was used instead of a sealed tungsten container. Here, the non-sealed container is a container with a structure in which a lid is simply placed on a main body.
[0106] Comparative Example 2 A phosphor powder of Comparative Example 2 was obtained in the same manner as in Example 2, except that in the firing step, a non-sealed container made of tungsten was used instead of a sealed container made of tungsten.
[0107] <Carbon content> The carbon content in the phosphor powder was measured by non-dispersive infrared absorption method using a carbon / sulfur simultaneous analyzer (CS-844, manufactured by LECO Co., Ltd.). The results are shown in Table 1.
[0108] <Composition> First, the phosphor powder was dissolved by the pressurized acid decomposition method to prepare a sample solution. Next, the obtained sample solution was subjected to quantitative element analysis using an ICP emission spectrometer (Shimadzu Corporation, ICPE-9000) to measure the molar ratios of Eu, Sr, Ca, Al, and Si contained in the phosphor powder. The results are shown in Table 1. Furthermore, 0.03 g of the phosphor powder was weighed out, and the oxygen and nitrogen contents were measured using an oxygen / nitrogen analyzer to determine the molar ratio of N and O. The results are shown in Table 1.
[0109] <Particle size> The particle size distribution of the phosphor powder was measured using a Microtrac MT3300EX II (Microtrac Bell) by the laser diffraction scattering method in accordance with JIS R1629:1997. Specifically, about 0.1 g of phosphor powder was put into 100 mL of ion-exchanged water, and a dispersion process was performed for 3 minutes using an Ultrasonic Homogenizer US-150E (Nihon Seiki Seisakusho, tip size φ20 mm, Amplitude 100%, oscillation frequency 19.5 KHz, amplitude approximately 31 μm), and then measurement was performed using the MT3300EX II. From the obtained particle size distribution, the D of the phosphor powder was determined. 50 , D 10 , D 90 and (D 90 -D 10 ) / D 50 The results are shown in Table 1.
[0110] <Diffuse reflectance> First, a UV-visible spectrophotometer (JASCO Corp., V-650) equipped with an integrating sphere device (JASCO Corp., ISV-722) was used to perform baseline correction with a standard reflector (Spectralon (registered trademark)), and a solid sample holder filled with phosphor powder was set in the holder, and diffuse reflectance was measured in the wavelength range of 450 to 800 nm. Next, the average value of the measurement results in the range of 700 nm to 800 nm was calculated, and this was taken as the average diffuse reflectance in the wavelength range of 700 to 800 nm. The results are shown in Table 1.
[0111] <Fluorescence spectrum> Fluorescence measurements were performed using a spectrofluorophotometer (Hitachi High-Technologies Corporation, F-7000) with correction using Rhodamine B and a secondary standard light source. Specifically, the phosphor powder was first filled into a concave cell so that the surface was smooth, and the cell was then attached to the opening of an integrating sphere. Next, monochromatic light with a wavelength of 455 nm was split from a Xe lamp, which is a light source, and introduced into the integrating sphere using an optical fiber as excitation light for the phosphor. The phosphor powder was irradiated with this monochromatic excitation light, and the fluorescence spectrum was measured using a spectrophotometer.
[0112] <Chromaticity> From the obtained fluorescence spectrum in the range of 465 nm to 780 nm, the x and y values of the CIE chromaticity coordinates in the XYZ color system defined in JIS Z8701:1999 were calculated in accordance with JIS Z8724:1997. The results are shown in Table 1.
[0113] <Peak wavelength, half-width, relative fluorescence intensity> From the obtained fluorescence spectrum, the peak wavelength and the half-width of the peak were obtained. In addition, from the peak intensity, the relative fluorescence intensity of the phosphor powder was also obtained. The results are shown in Table 1. Here, the relative fluorescence intensity was calculated by taking the peak height of the emission spectrum obtained by irradiating 455 nm monochromatic light onto YAG:Ce (P46Y3, manufactured by Kasei Optonix Co., Ltd.) as 100%, and expressing the peak intensity of the above fluorescence spectrum as the relative peak intensity (%). In other words, the relative fluorescence intensity is a relative value to the standard sample.
[0114] <Absorptivity, Internal Quantum Efficiency, External Quantum Efficiency> Using an instantaneous multi-photometer system (Otsuka Electronics, MCPD-7000), the fluorescence spectrum of the phosphor powder was measured in the same manner as the above-mentioned fluorescence spectrum measurement method. From the obtained fluorescence spectrum data, the emission intensity of the phosphor powder was determined, and the number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) were calculated. The number of excitation reflected light photons was calculated in the wavelength range of 450 to 465 nm, and the number of fluorescence photons was calculated in the range of 465 to 800 nm. In addition, using the same device, a standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was attached to the opening of the integrating sphere to measure the spectrum of excitation light with a wavelength of 455 nm. At that time, the number of excitation light photons (Qex) was calculated from the spectrum in the wavelength range of 450 to 465 nm. From the above calculation results, the absorptance Z of the phosphor powder for 455 nm light is calculated based on the following formula: 1 The internal quantum efficiency and external quantum efficiency were determined, and the results are shown in Table 1. Absorption rate Z for 455 nm light 1 =((Qex-Qref) / Qex)×100 Internal quantum efficiency = (Qem / (Qex-Qref)) x 100 External quantum efficiency = (Qem / Qex) x 100
[0115] The ratio of the raw materials is shown in Table 1. The ratio is the molar ratio when Al is taken as 1.000. In Table 1, the values in the columns Eu (molar ratio), Sr (molar ratio), Ca (molar ratio), Al (molar ratio), Si (molar ratio), and b / (b+c) do not include the elements in the core particles. The composition is the molar ratio when Al is set to 1.000.
[0116] [Table 1]
[0117] The phosphor powders of Examples 1 to 3 having a carbon content of 0.080 mass % or less had a relative fluorescence intensity of 211% or more, an internal quantum efficiency of 83.9% or more, and an external quantum efficiency of 70.0% or more. On the other hand, the phosphor powders of Comparative Examples 1 and 2, which had a carbon content exceeding 0.080 mass %, had a relative fluorescence intensity of 181% or less, an internal quantum efficiency of 70.9% or less, and an external quantum efficiency of 60.6% or less. From this, it can be seen that the phosphor powders of Examples 1 to 3 have improved light emitting properties compared to the phosphor powders of Comparative Examples 1 and 2.
[0118] 1. Phosphor powder 30 Encapsulating material 40 Complex 100 Light emitting device 120 Light emitting element 130 Heat sink 140 cases 150 First lead frame 160 Second lead frame 170 Bonding Wire 172 Bonding Wire
Claims
1. A phosphor powder comprising SCASN phosphor particles, The phosphor powder has a carbon content of 0.080 mass % or less as measured by a non-dispersive infrared absorption method using a carbon / sulfur simultaneous analyzer.
2. General formula, Eu a Sr b Ca c AlSi e N f O g 2. The phosphor powder according to claim 1 , comprising phosphor particles represented by the formula:
3. 3. The phosphor powder according to claim 2, wherein b>0.
500.
4. 4. The phosphor powder according to claim 2, wherein the molar ratio of b / (b+c) of the phosphor particles is 0.960 or more and 0.990 or less.
5. The phosphor powder according to claim 2 or 3, wherein a<0.
300.
6. The volume-based median diameter D of the phosphor powder measured by the laser diffraction scattering method 50 The phosphor powder according to any one of claims 1 to 3, wherein the particle size is 1.0 µm or more and 60.0 µm or less.
7. The particle diameter D at which the cumulative value reaches 10% in the volume frequency particle size distribution of the phosphor powder by the laser diffraction scattering method is 10 , 90% particle diameter D 90 , median diameter D 50 Regarding (D 90 -D 10 ) / D 50 The phosphor powder according to any one of claims 1 to 3, wherein the value of is 1.00 or more and 3.00 or less.
8. 4. The phosphor powder according to claim 1, which has an average diffuse reflectance of 90.0% or more at a wavelength of 700 to 800 nm as measured by an ultraviolet-visible spectrophotometer.
9. 4. The phosphor powder according to claim 1, wherein the x value of the luminescent color in the CIE chromaticity coordinates when excited with light having a wavelength of 455 nm is 0.550 or more and 0.650 or less.
10. 4. The phosphor powder according to claim 1, wherein the y value of the luminescent color in the CIE chromaticity coordinates when excited with light having a wavelength of 455 nm is 0.350 or more and 0.450 or less.
11. 4. The phosphor powder according to claim 1, wherein the peak wavelength of a fluorescence spectrum measured by a spectrophotometer when irradiated with light having a wavelength of 455 nm is 590 nm or more and 650 nm or less.
12. 4. The phosphor powder according to claim 1, wherein the half-width of the peak of the fluorescence spectrum measured by a spectrophotometer when irradiated with light having a wavelength of 455 nm is 80.0 nm or less.
13. A composite comprising the phosphor powder according to any one of claims 1 to 3 and a sealant that seals the phosphor powder.
14. A light emitting element that emits excitation light; The composite of claim 13, which converts the wavelength of the excitation light; A light emitting device comprising:
Citation Information
Patent Citations
Phosphor, light-emitting device, illumination device and image display device
JP2019077800A